Fear Thy Neighbor Radicalization and Jihadist attacks in the West - Eva Entenmann (Ledizioni, 2017)
Over the last three years Europe and North America have been hit by an unprecedented wave of terrorist attacks perpetrated by individuals motivated by jihadist ideology. Who are the individuals who have carried out these attacks? Were they born and raised in the West? Or were they an "imported threat", refugees and migrants? How did they radicalize? Were they well educated and integrated, or social outcasts? Did they act alone? What were their connections to the Islamic State? The answers to these and other questions have large implications for our understanding of the threat facing us and, consequently, help us design sounder policy solutions built on empirical evidence. This study, the first of its kind, seeks to analyze the demographic profile, radicalization trajectories and connections to the Islamic State of all the individuals who have carried out attacks inspired by jihadist ideology in North America and Europe in the three years since the proclamation of the caliphate in June 2014.